Immortal : a novel of the fallen angels - Ward, J. R., 1969- (Ward, J. R., 1969- Novel of the fallen angels., 2014)
"The Creator invented the game, and the stakes are nothing less than the fate of both the quick and the dead: seven souls, seven crossroads--each an opportunity for salvation or damnation. Coming into this sixth round, reluctant savior Jim Heron has compromised himself, his body and his soul, and even still, he's on the verge of losing everything.... And that includes Sissy, the innocent he freed from Hell. Jim's determined to protect her--but this makes her a weakness the demon Devina can exploit. With Sissy once again in danger, and Jim torn between the game and the woman he's sworn to defend, evil's ready to play dirty and finally claim Jim for her own. As the war comes into its final chapters, humanity's savior is prepared to do anything it takes to win--and that includes embarking on a suicide mission into the very darkest shadows of Purgatory. True love is Jim's only hope for survival--and victory. But can a man with no heart and no soul be saved by something he doesn't believe in?"--